A Mixed Method Study on the Dimensions of Teacher Mentoring as Correlates of Technical Assistance Performance of Master Teachers: A Future Ready Mentoring Program - Cherry Irene Escobal Agan (Randwick International of Education and Linguistics Science Journal, 2024)
The study investigated the correlation between the Dimensions of Teacher Mentoring and the technical assistance performance of Master Teachers, along with the facilitating and hindering factors within the Schools Division of Siargao. Key dimensions evaluated included mentoring structure, motivation, passion, system requirements, pedagogical competence, and feedback mechanisms. Using a mixed-method approach, 91 master teachers from 12 districts participated. Data collection involved questionnaires, interviews, and focus group discussions, with thematic analysis applied to qualitative data. Findings indicated high administrative support for mentoring structures, with master teachers showing strong motivation and competence. However, challenges such as inadequate internet connectivity, heavy workloads, and lack of resources hindered their performance. Despite these obstacles, master teachers exhibited a strong commitment to mentoring, though they faced significant distractions like health issues and multitasking. The study proposed an intervention program to address these challenges, emphasizing the need for improved administrative support, resources, and time allocation for mentoring activities. The conclusions drawn highlighted the importance of communication and professional development in enhancing mentoring effectiveness. Recommendations included institutionalizing mentoring programs, enhancing school-based mentoring initiatives, and conducting further research to refine and improve mentoring practices.